An 8-month adapted motor activity program in a young CMT1A male patient - Bottoni, Giorgio; Crisafulli, Oscar; Pisegna, Caterina; Serra, Marco; Brambilla, Sara; Feletti, Fausto; Cremonte, Giovanni; D’Antona, Giuseppe (Frontiers in Physiology, 2024)
ABSTRACT Background: It is unclear whether prolonged periods of training can be well tolerated. in Charcot-Marie Tooth disease (CMT). We report the effects of an 8-months, adapted motor activity (AMA) program in a 16-years-old CMT1A male patient. The program included strength, mobility, and balance training (2 sessions per week, 1 hour per session). Measures: Walking ability and walking velocity (Six-Minute Walking Test - 6MWT, Ten Meters Walking Test - 10mWT), balance (Y-Balance Test - YBT, Berg Balance Scale – BBS), functional mobility (Short Physical Performance Battery - SPPB), fatigue (Checklist Individual strength questionnaire - CIS20R), health and quality of life (Short Form Health Survey 36 questionnaire - SF-36) were evaluated in three moments: before (T0), after 5 (T1) and 8 (T2) months of AMA. Dorsal and plantar foot flexion strength (Maximal Voluntary Contraction - MVC) and neuromuscular functions (Electromyography - sEMG, interpolated twitch technique - ITT) were measured at T1 and T2. Results: Relative to T0, an amelioration of walking ability (6MWT, +9,3%) and balance (with improvements on Y-balance composite normalized mean reach of the right and left limb of 15,3% and 8,5%, respectively) was appreciable. Relative to T1, an increase in foot strength in 3 out of 4 movements (right plantar flexion, + 39,3%, left plantar flexion, +22,7%, left dorsal flexion, 11,5%) was observed. Concerning voluntary muscle activation, a greater recruitment in the left, unlike right, medial gastrocnemius was observed. Conclusion: Results suggest the safety of an 8-months AMA program in a young patient affected by CMT1A.